Front view of the Kalika Devi Temple - Temples of India Project Team (Jio Institute, 2024)
The exterior walls of the garbhagriha (sanctum sanctorum) of the Kalika Devi Temple are plain and devoid of decoration or sculptures. The entrance of the antarala (vestibule or antechamber) of the temple has carved pillars, and a few loose sculptures are placed at the entrance.